A Method for Measuring and Comparing the Mineral Sizes of Ores from Different Origins - Gottlieb P; Sutherland DN (The Australasian Institute of Mining and Metallurgy, 1988)
The paper describes a method of making quantitative mineralogical measurements on many of the major lead/zinc orebodies in Australia. The work was done using QEM*SEM. It was found that a relationship betwen phase-specific surface area and particle size, when plotted in a suitable way, gave a straight line with slope related to the grain size of the mineral in question. The method provides an excellent way of differen- tiating between minerals in existing orebodies and, consequently, an easy way to establish a comparison between a new prospect or orezone and current operations.